Exploring United Arab Emirates School Teachers’ Perceptions, Motivation and Benefits of Game-Based Teaching and Learning Environments - Murshidi, Ghadah Al; Wahyudi, Agus Budi; Islam, M Monjurul; Karthiga, S. V.; Rahmatika, Laily (Alberta Journal of Educational Research, 2024)
Recent research specifies that game-based learning effectively engages students in classroom activities. Although there has been a prominent upsurge in game-based teaching and learning, this area has not received significant attention within the context of Gulf nations. This study investigates the perceptions, motivations, and benefits of game-based teaching-learning among school teachers, aiming to enhance the interactive learning environment. This study used a quantitative method and survey data from 505 school teachers who were actively teaching around the United Arab Emirates to reach its objectives. The majority of teachers believed that using games as a teaching tool in the classroom was a good idea. The study revealed the potential for game-based learning in the classroom and identified challenges, such as the need for rigorous game-based instructional design. We examined game-based teaching and learning’s role in contributing to interactive learning environments and its apparent benefits of improving teamwork and lowering stress among teachers.